ACADEMIC INBREEDING OF COMMUNICATION SCIENCE PROGRAM STUDY IN INDONESIA - Bayu Indra Pratama; Kholidil Amin (Jurnal Penelitian Komunikasi dan Opini Publik, 2018)
Academic Inbreeding is a practice of educational institution which hires their graduates in their institutions. Research about Academic Inbreeding has been done in many countries. Academic Inbreeding research in Indonesia has not been done yet so far. The present research purposed to show the existence of Academic Inbreeding in Indonesia. Field of Communication which selected in this research because the number of doctoral program and master of communication science still limited. This problem brings up an assumption that the institutions which have doctoral program tend to have academic inbreeding. The result of his research found that academic inbreeding affected by geographical factors, historical factors, and university status.